Flow chemistry : integrated approaches for practical applications - Luis, S. V. (Santíago V.); García-Verdugo, E. (Eduardo) (RSC green chemistry series, 2020)
This volume provides an update on recent advances in the field of flow chemistry, with emphasis on new, integrated approaches for green and efficient chemistry.